Methods of Cancer Diagnosis, Therapy, and Prognosis Brain Cancer - Hayat, M. A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This eighth volume in the series Methods of Cancer Diagnosis, Therapy, and Prognosis discusses in detail the classification of the CNS tumors as well as brain tumor imaging. Scientists and Clinicians have contributed state of the art chapters on their respective areas of expertise, providing the reader a whole field view of the CNS tumors and brain tumor imaging in Europe. This fully illustrated volume: Explains the genetics of malignant brain tumors and gene amplification using quantitative-PCR; Presents a large number of standard and new imaging modalities, including magnetic resonance imaging, functional magnetic resonance imaging, diffusion tensor imaging, amide proton transfer imaging, positron emission tomography, single photon emission computed tomography, magnetic resonance single voxel spectroscopy and intraoperative ultrasound imaging, for staging and diagnosing various primary and secondary brain cancers; Explains the usefulness of imaging methods for planning and monitoring (assessment) therapy for cancers; Discusses diagnosis and treatment of primary CNS lymphomas, CNS atypical teratoid/rhabdoid and CNS Rosai-Dorfman disease; Includes the subject of translational medicine. Professor Hayat has summarized the problems associated with the complexities of research publications and has been successful in editing a must-read volume for oncologists, cancer researchers, medical teachers and students of cancer biology.
Keywords: Medicine; Oncology; Radiotherapy; Nursing; Cancer -- Surgery; Biomedicine; Cancer Research; Oncology; Surgical Oncology; Nursing; Radiotherapy